2013
DOI: 10.1115/1.4007800
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tip Clearance Momentum Flux on Stall Inception in a High-Speed Axial Compressor

Abstract: Experimental and numerical studies were conducted to investigate tip-leakage flow and its relationship to stall in a transonic axial compressor. The computational fluid dynamics (CFD) results were used to identify the existence of an interface between the approach flow and the tip-leakage flow. The experiments used a surface-streaking visualization method to identify the time-averaged location of this interface as a line of zero axial shear stress at the casing. The axial position of this line, denoted xzs, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Vo [2] found that a criterion for spike-type stall inception is that the interface created from the approach flow and the reverse tip-leakage flow becomes parallel with the rotor leading edge plane. Later Cameron et al [3] obtained measurements supporting this concept using the compressor used in the present work. Tan et al [4] provide a comprehensive review on the current understanding of stall inception.…”
Section: Introductionsupporting
confidence: 54%
“…Vo [2] found that a criterion for spike-type stall inception is that the interface created from the approach flow and the reverse tip-leakage flow becomes parallel with the rotor leading edge plane. Later Cameron et al [3] obtained measurements supporting this concept using the compressor used in the present work. Tan et al [4] provide a comprehensive review on the current understanding of stall inception.…”
Section: Introductionsupporting
confidence: 54%
“…13 Based on this result, it is reasonable to conjecture that circumferential groove casing treatments (CGCT) increase surge margin by altering the axial momentum balance through their interaction with the tip clearance flow field, namely through radial transport of axial momentum. This paper examines this hypothesis through the findings of experiments conducted on a high-speed, single stage axial compressor with several circumferential groove casing treatment geometries as well as information available from simulations of the compressor rotor with a smooth wall.…”
Section: Introductionmentioning
confidence: 92%
“…As for the rotor limiting streamlines, it is observed that the vortex flow region of RANS solution dominates in hub region. However, the vortical flow motions occur (6) where Ω is vorticity magnitude, S is mean strain rate. It is found that the two vortex structures predicted by RANS and DES are clearly different from each other as seen in Figs.…”
Section: (5)mentioning
confidence: 99%
“…They discovered that the cyclical motion of tip secondary vortex was the main source of the nearly periodic variation of efficiency. Cameron et al [6] studied the role of tip leakage flow in axial compressor stall by the experiments and computations. The results confirmed that the compressor stalled when an interface between the approach flow and the tip-leakage flow reached the rotor leading edge plane as flow coefficient was reduced.…”
Section: Introductionmentioning
confidence: 99%